STUDI ANALISIS NILAI-NILAI KESETARAAN GENDER DALAM SURAT AL-MUJADALAH AYAT 1-4 - Nurmiah (STAI Al-Mujtama Pamekasan, 2023)
Gender equality begins to be felt by women as a form of discrimination that comes from an uncontrolled patriarchal culture. Many classical literary traditions have left behind patriarchal culture, therefore this article discusses the issue of husband-wife gender equality in the Qur'an. For example, the wife is often positioned as a person who gets harsh, unfair and discriminatory treatment, even though if examined in QS. MujÄdalah [58]: 1-4 shows how God is very concerned about women who receive bad treatment from their husbands. This study aims to explore gender equality in QS. MujÄdalah [58]: 1-4. This research is a library research or library research using gender analysis. The results of the research show that QS. al-MujÄdalah [58]: 1-4 teaches about the emancipatory spirit. Emancipatory is equal rights, respecting life, both women and men, all of them get the same treatment in the sight of Allah, the only difference is their piety, men and women are present not to prove each other, to contest who is more right.Keywords: Gender, Gender Equality, Al-Mujadalah